CATALYZING QUALITY ACADEMIC RESEARCH THROUGH NEW EDUCATION POLICY: PATH FOR IMPLEMENTATION - Tripathi, Vivek Nath; Jaiswal, Sonali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Academic community of the nation has been invigorated by the announcement of New Education Policy, 2020. The community has started forwarding findings over the implementation issues of the policy. The policy has shown right destination, and now we have to find a potential path to reach that destination. Any policy is as successful as its implementation. The current article discusses the issues present in academia and proposes suggestions concerning the implementation of New Education Policy for the amelioration of academic research. The authors highlighted the issues of silo formation, admission criteria, funding, curricula designing, reskilling of teachers and skilling of students, infrastructure and resources, post-doc culture, internationalization, including immigration, emigration, and reverse migration, and maintaining the balance between research and innovation.